Trends of youth towards civil marriage (Field study on a sample of students of the Department of Sociology) - Dalala, Mirna; Salloum, Loay (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The purpose of the research is to identify the trends of university youth towards civil marriage, and to know the extent of the influence of some factors such as education and the presence of civil marriage cases within the large family in the acceptance of young people to the idea of associating a life partner from outside their religion or doctrine. Did legislation in both Christian and Islamic religions hindered this type of marriage? And to what extent does the media play the role in accepting or rejecting the idea? The researcher designed a questionnaire that was applied to a sample of 30 students from the Department of Sociology at Tishreen University. The results of the study show the following: It was found that there is acceptance of the idea of civil marriage by a large part of the sample studied but they prefer and encourage religious marriage, and that the education and study at the university and the social environment play a large role in accepting this type of marriage. It turns out that a large proportion of the sample find that the media plays a large role in accepting the idea of civil marriage, and that religious legislation plays a major role in the alienation of society from this kind of marriage.